Development of tissue engineering grafts for osteochondral regeneration - Nie, Xiaolei (2019)
Tissue engineering is the combination of cells, biomaterials and growth factors to stimulate the regeneration of damaged tissue or replace the dysfunctional tissue. Since the first success of proliferation of keratocytes in vitro, tissue engineering grafts have been regarded as a promising alternative method to current allo-, auto- or xeno-graft treatment for loss of osteochondral tissue due to injury. Although widely applied, allo and xeno grafts bares the risk of disease transmission and immune rejection, whereas auto graft faces the challenge of limited source and donor site morbidity. In addition, due to the dense nature of osteochondral tissue, native tissue derived grafts meets the problem of integration with surrounding tissue. Hence tissue engineering grafts are attracting more and more attention as methods to repair osteochondral defects. Osteochondral tissue consists of two different types tissue, i.e. cartilage and subchondral bone, clapping a transition zone in between. Hence to develop a full-scaled graft with two different phases matching the cartilage and bone respectively and a transition zone in the interface is critical to the success of the field. On the other hand, when entering clinical application, living tissue engineering grafts bring about problems in logistics and cell sources. Therefore, decellularized tissue engineering grafts become popular as an acellular version of osteochondral grafts, where the cells were removed, and the extracellular matrix were retained. In the first instance, the biphasic grafts with a naturally formed interpenetration network as the transition zone was fabricated by using sintered poly (lactic-co-glycolic acid) microspheres scaffold as the subchondral bone phase and microcavity 3D chondrocytes culture system to generate the cartilage phase. The interpenetration network was formed by the natural cell migration process from the cartilage phase to the subchondral bone phase in the graft maturation. To overcome the hurdle brought about by cellular nature of the graft including biocompatibility and logistics difficulty, the graft was decellularized to generate an acellular version of the biphasic grafts. Its capacity to repair osteochondral defect was evaluated in rabbit knee injury model. In the second instance, a scaffold-free graft fabricated using a transient scaffold named living hyaline cartilage graft was decellularized to make an acellular hyaline like manmade cartilage graft which broadens the cell source and circumvent the hurdles in clinical regulation. A combination of physical, chemical and biological methods has been applied on the living hyaline cartilage graft to generate decellularized manmade hyaline cartilage graft which was evaluated for the capability to repair both cartilage defect and osteochondral defect in both pig and rabbit animal models. The graft has been shown to regenerate cartilage and subchondral tissue in the defect with the same morphology and composition as native cartilage and subchondral bone tissue. In addition, the thorough integration to the surrounding tissue has been exhibited. These results are due to the dual advantages of genuineness in phenotype, composition and architecture of the graft to native cartilage and high porosity to facilitate cell migration which eventually leads to the recovery of the function of osteochondral tissue, i.e. the mechanical strength. In summary, the tissue engineering grafts were characterized and the efficacy to repair osteochondral grafts were evaluated. It was found that the biphasic tissue engineering living grafts were able to repair osteochondral defects successfully whereas the decellularized hyaline-like cartilage graft was able to repair both cartilage and osteochondral defects successfully. Collectively, the results implied the sufficiency of using cartilage graft to repair osteochondral defects which requires further detailed study to elucidate the mechanism.